2007
DOI: 10.1093/ndt/gfl753
|View full text |Cite
|
Sign up to set email alerts
|

Association of genotypes of thrombin-activatable fibrinolysis inhibitors with thrombotic microangiopathies--a pilot study

Abstract: The results of our pilot study indicate that the GG genotype of the C1542G polymorphism of TAFI displays risk factors for the manifestation of thrombotic microangiopathies. Our observation provides a rationale to assess genotype-phenotype relations by determination of TAFI plasma levels in various stages of disease in patients suffering from these rare thrombotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…36 We tested the effect of the thrombomodulin variants on thrombin-mediated generation of TAFIa, as assessed by the appearance of a 36-kD fragment 37 (Fig. 5C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36 We tested the effect of the thrombomodulin variants on thrombin-mediated generation of TAFIa, as assessed by the appearance of a 36-kD fragment 37 (Fig. 5C).…”
Section: Resultsmentioning
confidence: 99%
“…The additional impairment in TAFIa generation probably aggravates the disease. 36 Thrombomodulin has a binding site for C3b and CFH, thereby accelerating CFI-mediated inactivation of C3b. Beyond these activities, which negatively regulate the alternative pathway, thrombomodulin plays a wider role in suppressing complement-mediated cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…While one study found that the 147Thr allele of the Ala147Thr polymorphism protected against MI [27], in another study, the 147Thr allele was associated with a higher risk of angina [28]. TAFI polymorphisms C+1542G and Thr325Ile were also found to be related to the type of ACS [29] and thrombotic microangiopathies [30]. Regarding cerebrovascular diseases, Akatsu et al did not find any association between the Ala147Thr and Thr325Ile polymorphisms of TAFI and cerebral infarction [18].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recently, we identified the GG genotype of the G1642A polymorphism of the thrombin-activatable fibrinolysis inhibitor (TAFI), an important regulator at the interface of fibrinolysis and inflammation, and the homozygous Leu variant of the factor XIII Val34Leu polymorphism as another factor predisposing to the onset of thrombotic microangiopathies. 6 In the presented study, we focused on the potential role of prothrombotic variants of platelet receptor polymorphisms in the pathogenesis of thrombotic microangiopathies. Respective polymorphisms of platelet receptors involved in platelet adhesion and aggregation were shown to modulate platelet thrombogenicity in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%